2021
DOI: 10.1080/00913847.2021.2004080
|View full text |Cite
|
Sign up to set email alerts
|

Pre-race self-reported medical conditions and allergies in 133 641 Comrades ultramarathon (90km) runners - SAFER XXIII

Abstract: Objectives: To determine the prevalence of self-reported pre-race chronic medical conditions and allergies in ultramarathon race entrants and to explore if these are associated with an increased risk of race-day medical encounters (MEs).Methods: Data from two voluntary open-ended pre-race medical screening questions (Q1history of allergies; Q2 -history of chronic medical conditions/prescription medication use) were collected in 133 641 Comrades Marathon race entrants (2014)(2015)(2016)(2017)(2018)(2019). Race-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…However, no scientific evidence supports the use of two screening questions to identify runners at risk for MEs on race day. We recently showed that the positive responses to these questions are predictive of MEs on race day, but that the voluntary completion of two open‐ended questions was considerably lower than that reported for other races that implemented compulsory completion of a more comprehensive pre‐screening questionnaire 23 . Currently, it is unknown to what extent the information from the abbreviated tool (two open‐ended medical questions) during the race entry process compares to a full and comprehensive pre‐race medical screening questionnaire.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, no scientific evidence supports the use of two screening questions to identify runners at risk for MEs on race day. We recently showed that the positive responses to these questions are predictive of MEs on race day, but that the voluntary completion of two open‐ended questions was considerably lower than that reported for other races that implemented compulsory completion of a more comprehensive pre‐screening questionnaire 23 . Currently, it is unknown to what extent the information from the abbreviated tool (two open‐ended medical questions) during the race entry process compares to a full and comprehensive pre‐race medical screening questionnaire.…”
Section: Introductionmentioning
confidence: 88%
“…Another medical doctor independently checked a subset of the responses for reliability. This coding process and reliability have previously been described in detail 23 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations